2020
DOI: 10.1016/j.heliyon.2020.e04163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traditional and improved solar drying methods on the sensory quality and nutritional composition of fruits: A case of mangoes and pineapples

Abstract: Background: This study investigated the effect of traditional and improved solar drying methods on the sensory quality and nutritional composition of the dried fruit products; using mangoes and pineapples, as a case study. The fruits were dried under five solar drying methods namely; open sun drying (OSD), black-cloth shade (BCS), whitecloth shade (WCS), a conventional solar dryer (CSD), and a newly improved solar dryer (ISD) technology. The ISD unit was made of a modified solar concentrator plate containing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 25 publications
2
65
0
5
Order By: Relevance
“…(2018) , who found significant increase of titrable acidity of frozen apricots during storage of 90 days. Mohammed et al. (2020) have also reported an increase of acidity in mango and pineapples dried in various methods.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…(2018) , who found significant increase of titrable acidity of frozen apricots during storage of 90 days. Mohammed et al. (2020) have also reported an increase of acidity in mango and pineapples dried in various methods.…”
Section: Resultsmentioning
confidence: 86%
“…These decreases may be due to non-enzymatic browning reactions occurring during thermal processing of fruit samples. Mohammed et al. (2020) found also a variation of total carbohydrates and sugars content when mango and pineapples were subjected to different drying methods.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Applied higher temperatures and prolonged exposure to oxygen could ultimately decrease vitamin content during the drying of fruits [78]. Nevertheless, one study concluded that applied solar drying even at lower temperatures (24.5-40.3 • C) could significantly (p < 0.05) reduce the vitamin content in the fruits [79]. Due to dehydration of the pieces to a moisture level of 10% or even lower, the relative increases in the concentrations of the mineral content, total acidity, carbohydrates and total sugars were significantly higher in the dried fruits as compared to the fresh samples.…”
Section: Chemical Qualitymentioning
confidence: 99%
“…Pineapple is one of the most desired and generally consumed succulent non-citrus fruits, mainly for its splendid sensorial characteristics and revitalizing sugar action. It has been considered as a vibrant source of the essential nutritients, such as minerals, vitamins (vitamin C, thiamine, vitamin B 6 , folate), antioxidants, dietary fiber, etc ( Mohammed et al., 2020 ; Bartolomé et al., 1995 ; Ramallo and Mascheroni, 2012 ). The demand of pineapple for internal consumption and also for export is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%